REPRESENTATIVE AND ILLUMINIST CONSTITUTIONAL JURISDICTION: AN OUTLOOK BASED ON THE HERMENEUTICAL CRITICISM OF LAW - Rodrigues, Josenilson (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
The present study analyzed the representative and illuminist role of the Constitutional Courts (Barroso) under the lens of the Hermeneutic Criticism of Law (Streck). The objective was to understand, based on these theoretical matrices, what to expect from Brazilian constitutional jurisdiction to adequately meet the constitutional project inaugurated in 1988. An approach was made to the representative and illuminist role of the Constitutional Courts and the Hermeneutic Criticism of Law (HCL) and, at the end, an analysis of the representative and illuminist role of the Constitutional Courts based on the HCL. It was noted that HCL offers elements that are best suited to the democratic implementation of the constitutional project inaugurated in 1988.